IMPLEMENTASI TANDA TANGAN ELEKTRONIK PADA WEBSITE SISTEM INFORMASI KEPEGAWAIAN (SIMPEG) KABUPATEN SAROLANGUN: Electronic Signature, Website, Information System, BSrE - Husna Ahadi, Ahmad; Gustina (LP2M Universitas Nurdin Hamzah, 2023)
Sarolangun Regency through its agency, namely Badan Kepegawaian dan Sumber Daya Manusia (BKPSDM), has a website called the Sistem Informasi Kepegawaian (SIMPEG) which aims to provide public services such as filing for leave and filing periodic salaries for employees within the Sarolangun Regency government. Currently the submission process has been made through the system but has not been able to validate documents electronically. Therefore, a mechanism is needed to validate the document using an electronic signature. This electronic signature is a solution and has been provided by a Government agency called the Balai Sertifikasi Elektronik (BSrE). The research method used in this research is the waterfall method. In this research, a system design and its implementation will be made so that the SIMPEG website can process the electronic signature of the BSrE.